Polar-Axis Orientation Fluctuations and the Impact on the Intrinsic Variability in Ferroelectric Capacitors - Wei Zhang; Jianze Wang; Xuanyao Fong (IEEE Journal on Exploratory Solid-State Computational Devices and Circuits)
We utilized phase-field simulations to investigate the effects of polar-axis (PA) orientation fluctuations on the extrinsic properties of single ferroelectric (FE) grains, focusing on the coercive electrical field (EC) and the remnant polarization (Pr). The underlying mechanisms through which PA orientation fluctuations influence polarization behavior are studied to gain insights into variations in FE device performance and reliability. In addition, we used the Voronoi algorithm to simulate multigrain (MG) FE capacitors and assess the impact of PA orientation fluctuations on the device variability of polycrystalline FE capacitors. Our analysis shows that the PA orientation, which is a significant intrinsic factor, collectively contributes to device variability. We conclude that engineering the PA orientation helps to optimize FE device performance and reliability, which is crucial for the development of high-performance FE memory technologies.